Redesign and reconstruction of a mevalonate pathway and its application in terpene production in Escherichia coli - Choi, Bo Hyun; Kim, Jin Ho; Choi, Sun Young; Han, Se Jong; Lee, Pyung Cheon (Bioresource Technology Reports, 2019)
Metabolic engineering of heterologous biosynthetic pathways in microbial hosts is an alternative way for producing high-value biochemicals. Here, heterologous mevalonate (MVA) and prenyl pyrophosphate (IPP) pathways of a new isolate Enterococcus kingsejongensis Gf1 were redesigned and reconstructed in Escherichia coli. Two MVA upstream enzymes of E. kingsejongensis Gf1 were functionally expressed and overexpression of the two enzymes led to a yield of 52.5 g/L MVA after 65 h of fed-batch fermentation. Next, the functions of three MVA downstream enzymes were verified by addition of exogenous MVA. Finally, whole MVA pathway enzymes and IPP pathway enzymes were combined in E. coli in order to overproduce squalene and β-carotene. The E. coli strains coexpressing entire MVA and IPP pathway enzymes enhanced squalene production by 15-fold and β-carotene production by 2.5-fold.
Keywords: Biosynthetic pathway; Enterococcus; Fed-batch fermentation; ITS applications; Mevalonate; Mevalonate pathway; Over-expression; Pathway engineerings; Enterococcus; Mevalonate; Pathway engineering